2019
DOI: 10.1093/molbev/msz174
|View full text |Cite
|
Sign up to set email alerts
|

The Current Genomic Landscape of Western South America: Andes, Amazonia, and Pacific Coast

Abstract: Studies of Native South American genetic diversity have helped to shed light on the peopling and differentiation of the continent, but available data are sparse for the major ecogeographic domains. These include the Pacific Coast, a potential early migration route; the Andes, home to the most expansive complex societies and to one of the most widely spoken indigenous language families of the continent (Quechua); and Amazonia, with its understudied population structure and rich cultural diversity. Here, we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 89 publications
13
69
0
5
Order By: Relevance
“…The percentage of total variation explained by each PC is shown in parentheses on each axis.
Figure S4 PCA of Additional Samples Removed from Figure 2 , Related to Figure 2 Principal Components Analysis (PCA) of ancient samples projected onto modern individuals from the Andes and Amazon region ( Barbieri et al., 2019 ). Eigenvector 1 coordinates were reversed so that the PCA correlates with geographical structure.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of total variation explained by each PC is shown in parentheses on each axis.
Figure S4 PCA of Additional Samples Removed from Figure 2 , Related to Figure 2 Principal Components Analysis (PCA) of ancient samples projected onto modern individuals from the Andes and Amazon region ( Barbieri et al., 2019 ). Eigenvector 1 coordinates were reversed so that the PCA correlates with geographical structure.
…”
Section: Resultsmentioning
confidence: 99%
“… Principal Components Analysis (PCA) of ancient samples projected onto modern individuals from the Andes and Amazon region ( Barbieri et al., 2019 ). Eigenvector 1 coordinates were reversed so that the PCA correlates with geographical structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Archaeological findings of recent decades have rejected the traditional view of the Amazonian environment as incompatible with complex pre-Columbian societies, and have revealed that the Amazonian basin has produced the earliest ceramics of South America, that endogenous agricultural complex societies have developed there, and that population sizes were larger than previously thought 22 . Population genetics studies by Barbieri et al 23 have reported episodes of gene flow in the Amazonia, which suggest that Amazonian populations were not necessarily isolated groups. Moreover, people living in the Peruvian Coast, the Andes, and the Amazon Yunga had cultural and commercial interactions during the last millennia, sharing practices such as sweet potato and manioc cultivation, ceramic iconography and styles (e.g.…”
Section: Inferred That Andean Andmentioning
confidence: 99%
“…Esto brinda apoyo a algunos trabajos previos que describieron la existencia de una varianza baja entre poblaciones de los Andes, fundamentalmente debida a aislamiento geográfico, especialmente entre muestras de los andes/amazonia, y/o costa/sierra (Hrdlička 1911(Hrdlička , 1914Newman 1943;Tarazona-Santos et al 2001;Ross et al 2008). Dicho patrón puede ser resultado de dinámicas poblacionales con matrimonios preferenciales basadas en la exogamia y/o exoginia, tal como ha sido reportado recientemente para poblaciones de los Andes, Amazonia, y la costa Pacífica, basados en una combinación de datos genéticos y lingüísticos (Arias et al 2017(Arias et al , 2018Barbieri et al 2019). La presencia de sociedades de gran escala, tanto en los Andes como en la costa, puede haber promovido el flujo génico entre individuos, así como también combinado poblaciones que carecían de contacto previo o que era muy esporádico.…”
Section: Discussionunclassified